Cultural Variation in the Effectiveness of Feedback on Students’ Mistakes - Eriksson, Kimmo; Lindvall, Jannika; Helenius, Ola; Ryve, Andreas (Frontiers in Psychology, 2020)
One of the many things teachers do is to give feedback on their students’ work. Feedback pointing out mistakes may be a key to learning, but it may also backfire. We hypothesized that feedback based on students’ mistakes may have more positive effects in cultures where teachers have greater authority over students. To test this hypothesis we analyzed data from 49 countries taking part in the 2015 wave of the TIMSS assessment, in which students in grades 4 and 8 were asked whether their teachers in mathematics and science told them how to do better when they had made a mistake. For each country we could then estimate the association between mistake-based feedback and student achievement. Consistent with our hypothesis, this association only tended to be positive in countries that are high on religiosity, power distance, and collectivism. These results highlight the importance of cultural values in educational practice.